Idiopathic chondrolysis of hip: a case report - M.M.R., Sandeep; Jose, Ashish Kumar; Kumar, Surendher; M., Chandrasekaran; R., Krishnagopal (International Surgery Journal, 2016)
Idiopathic chondrolysis of the hip is a rare condition occurring mainly in adolescents and is characterised by a rapidly progressive destruction of the articular cartilage. A male patient aged 18 years presented to us with pain in his left hip, restriction of movements, and limping due to pelvic obliquity. On examination patient had severe tenderness over left hip, fixed flexion and abduction deformity were present and all movements were painful. Radiographic imaging showed narrowing of joint space, irregular blurring of subchondral sclerotic lines and femoral neck widening. MRI scan depicts marrow changes earlier than any other imaging method. Biological markers for inflammation and infections have been studied, which was normal. To achieve mobile hip, for this patient we planned for Total hip replacement after confirming our diagnosis. Idiopathic chondrolysis of the hip is a rare clinical entity where, unfortunately, there is often a delay in diagnosis. There are characteristic clinical and radiological features but no effective therapy to arrest the disease. Until today no evidence concerning the aetiology of ICH has been presented. Therefore the treatment is mainly symptomatic. Conservative treatment focuses on pain control and preservation of joint mobility. Physiotherapy seems to be important to preserve a good range of motion. In addition most authors agree to unload the affected hip joint by means of bed rest and skin traction. Published results of surgical treatment are not conclusive and arthroplasty in young patients is controversial. There is no consensus on the treatment algorithm. Recommended surgical treatments include corrective osteotomy, bony fusion or joint arthroplasty. Awareness of the existence of this disease will lead to earlier diagnosis and management.